The Meaning of וַַיַַּעַַל בְְּכָָל־הָָאָָרֶֶץ in 2 Kgs 17:5a. The Semantic and Syntactic Study of the Phrase with Particular Interest in the Verb עלה and the Preposition בְְּ - Kinowski, Krzysztof (The Biblical Annals, 2023)
The expression וַיַַּעַַַל בְְּכָָל־הָָאָָרֶֶץ in 2 Kgs 17:5a is apparently simple and devoid of semantic or syntactic difficulty. This Hebrew phrase is, however, interpreted variously by the scholars who generate a considerable plurality of its translations. The problem appears to lie in the diversity with which the meaning of the verb √ עלה and of the preposition בְְּ, and further, their semantic and syntactic relation in 2 Kgs 17:5a, are interpreted. The examination of these lexemes’ semantics and their interrelated syntax in the Hebrew text leads to the following conclusions: (1) the verb √ עלה has there a technical-military meaning “to invade, attack, march against;” (2) it is used stereotypically and from the sociolinguistic perspective it denotes the nuance of an upward movement; (3) the meaning of בְְּ is spatial in 2 Kgs 17:5a and marks an area moved through; (4) the syntactic relation √ בְּ + עלה is not equivalent to √ עַל + עלה , and consequently, the technical-military meaning of the verb does not remove the spatial meaning of the preposition. It is proposed to translate 2 Kgs 17:5a in a following way: “And then (the king of Assyria) marched up throughout the whole country.” Such a rendering expresses both the Assyrian military actions, a physical movement upwards, and the area moved through. From the historical point of view, it describes the first stage of the Assyrian attack, the invasion going throughout the whole country of king Hosea (v. 5a), followed by an attack directed against its capital, Samaria (v. 5bc). Other interpretations (translations), either ignoring or highlighting one of the discussed features only, may be considered incomplete, questionable or unacceptable from the semantic and syntactic point of view.